DIREITO INTERNACIONAL DOS DIREITOS HUMANOS E O DIREITO DE CIRCULAÇÃO DOS POVOS INDÍGENAS EM MOBILIDADE TRANSFRONTEIRIÇA NO ESTADO DE MATO GROSSO DO SUL - LUYSE VILAVERDE ABASCAL MUNHÓS (2022)
The phenomenon of cross-border mobility is a customary practice related to the “walker” way of being characteristic of Guarani and Kaiowá cosmology, being essential for the maintenance of culture, identity and, consequently, for the guarantee of a dignified life, as it is related to processes of identity construction, collective memory and social and community ties. The conceptual formulation of cross-border mobility as a cultural phenomenon is drawn from interdisciplinary studies with Anthropology, since, when it comes to rights conferred on indigenous peoples, it is necessary to adopt an approach that provides subsidies to understand the cultural practices of these peoples, through perspective of alterity and diversity. According to the parameter of interculturality of human rights, provided by the Critical Theory of Law, it is clear that the cross-border displacement of the Guarani and Kaiowá peoples is nothing more than the exercise of the right to come and go under a new perspective, as it is not related with individual liberties, but rather the collective character of the right to the territory traditionally occupied. From this perspective, the cultural practice of circulation in the ancestral territory ends up recognizing ethnic-cultural borders that transcend the limits of states, since the identity element of indigenous peoples demands the recognition of the category of indigenous ethnocitizenship, guided by ethnic belonging, which materializes in the factual world in a transnational way. It so happens that such conceptions of the world come into conflict with the official logic of legal dogmatics, resulting in the collision between the state constitutional order and the reality of indigenous peoples, treated by the present work as an extra-state normative order. A clear example of this collision is the presidential veto of paragraph 2 of art. 1 of the Migration Law, which ended up contradicting international treaties to which Brazil is a signatory, failing to recognize the cross-border mobility of indigenous peoples as an original right and denying legal protection to indigenous families who practice mobility. The research takes as a problem the following question: is it possible to say that the Brazilian domestic legal system recognizes the right of indigenous peoples to move in cross-border mobility? The relationship between International Human Rights Law, the Inter-American System of Human Rights and Brazil, provides the assumption that the absence of legal recognition of the right of movement of indigenous peoples by the Migration Law represents a posture of non-compliance with the inter-American and international law, but this is not the same as saying that this right does not exist in the national domestic order. Therefore, the general objective is to analyze the recognition of the right of movement of indigenous peoples in cross-border mobility based on International Human Rights Law (IDHR) and the Inter-American System of Human Rights (IAHR). The methodological guidance is given through descriptive and exploratory research, the hypothetical-deductive method and bibliographic and documental analysis, based on books, articles, declarations and international conventions.